Tripolitania, Cyrenaica, and Bilad as-Sudan: Trade relations during the second half of the nineteenth Century - Fituri, Ahmed Said (University of Michigan, 1982)
Keywords: Commerce transsaharien

Soninke-Ibāḍiyya interactions in the western Sudan c. ninth to c. eleventh century - Perinbam, B. Marie (The Maghreb Review, 1989)
This paper investigates cultural interactions between the Soninke of Ghana (or Wagadu kingdom) and the Maghribī Ibāḍiyya in the western Sudan, from about a century before, to approximately a century after the Almoravid confederation in the western Sahara. From the late 8th and early 9th centuries, the Ibāḍiyya, together with other Berberophone populations, moved south into the upper Senegal and Niger river regions, primarily engaging in commercial and missionary activities. They usually stayed in towns or Muslim quarters near urban settlements such as Tahert, Wargla, and Gao, where they came into contact with Soninke traders. The degree to which Soninke-speakers may have been influenced by the Ibāḍī religion is not clear, but available evidence suggests that some pre-Almoravid conversions occurred. However, after the 11th century, the Almoravids effectively removed most traces of the Ibāḍī doctrine (Catalogue African Studies Centre, Leiden).
Keywords: Commerce transsaharien

Were the Maghribi Ibāḍiyya contributors to West-African food production? An evaluation of the evidence - Perinbam, B. Marie (The Maghreb Review, 1987)
While acknowledging that sub-Saharan Africa was the site of early food production, this paper evaluates the evidence that the production of some North-African Mediterranean and Asian food crops was introduced into West Africa by the little known Ibāḍiyya -the oldest of all Islamic sects- from Maghribian communities, possibly between the 8th and 16th centuries. In answering the question “how” or “by what process” Maghrib foods were diffused across the Sahara, the paper argues for the existence of Ibāḍī diasporas before the 10th century when Trans-Saharan commercial networks first began to be organized, thereby fueling important changes in the desert’s political economy (Catalogue African Studies Centre, Leiden).
Keywords: Commerce transsaharien

The role of the Sahara and Saharians in relationships between North and South - Lewicki, Tadeusz (General history of Africa: Africa from the Seventh to the Eleventh century, 1988)
Keywords: Commerce transsaharien

العلاقات الأقتصادية والثقافية ببن الدولة الرستمية وبلدان جتوب الصحراء الكبرى وائرها في نشر الإسلام هناك - الحرير, ادريس صالح (مجلة البحوث التاريخية, 1983)
Keywords: Commerce transsaharien

Jerba, Bou-Grara et la question du commerce transsaharien, à la fin du XIXe Siècle - ʿAnnābī, Ḥasan al- (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Commerce transsaharien